Nécropoles et société au premier âge du Fer Le tumulus de Courtesoult (Haute-Saône) - Piningre, Jean-François (Documents d'archéologie française, 1996)
A large campaign of excavations has saved the gaulish tumulus of Courtesoult (Haute-Saône) from destruction. These researches have put into evidence two main phases of construction and use of the monument which includes 45 tombs. These have been the subject of detailed anthropological and palaeodentographical studies. The typological analysis of the small finds, mainly composed of dress items (brooches, bracelets, belt hooks, coral beads), gives a date ranging from the Hallstatt D1 to the La Tène A period. The data From Courtesoult can be put up against that of other burial sites, such as Gy, Mantoche or Savoyeux. It gives further details concerning the evolution of funeral practices from the first Iron Age in the region between the Jura and Burgundy. This area had hitherto given rise to no recent research far this period.